Physical and ultra-structural attributes of bulls' semen with variable freezing potential - Mada, Khumran Armiya'u; Degu, Nurhusien Yimer; Yusoff, Rosnina; Omar, Mohamed Ariff; Haron, Abd Wahid; Ebrahimi, Mahdi; Kaka, Asmatullah; Mahre, Mohammed Bakari (2015)
Experiment was conducted on four breeding and research bulls (numbered 1 to 4) at the Universiti Putra Malaysia (UPM) farm to determine the physical and ultra-structural attributes of their fresh semen. A total of 40 semen samples (10 from each bull) were collected by electro-ejaculation method. The semen samples were examined for colour, volume, pH, sperm concentration, general and progressive motilities, normal morphology, acrosome and DNA damage, and lipid peroxidation. Transmission Electron Microscopy (TEM) was also used to evaluate ultra-structures of their spermatozoa. Results revealed that semen colour varied among individual bulls. Highest sperm concentration, lipid peroxidation and pH were recorded from bull #4. Highest volume, progressive motility, morphology, less acrosome damage and viability were recorded from bull #2. While the best values for general motility and DNA damage were recorded from bull #1. TEM identified 32.5, 25, 37 and 80% of ultra-structural sperm damages to bulls #1, 2, 3 and 4 respectively. Conclusively, bulls #1, 2 and 3 results were consistently satisfactory in most parameters evaluated and hence can be used for freezing. On the other hand, bull #4 expressed significantly (p < 0.05) higher sperm concentration but yet unsatisfactory in most other tests conducted. Such poor result of bull #4 may not be unconnected with the low live/dead ratio and high abnormalities recorded from both morphology and TEM of the bull’s sperm manifesting poor potential of freezability.